Malaysian Rural ESL Learners’ Perceived English Language Proficiency - Muhamad, Maizatulliza; Hock Seng, Goh; Natchiar Mohd Khaja, Farah; Haniff Mohd Tahir, Mohd; Saputra, Syahwil (Arab world English journal, 2024)
English is a compulsory subject taught in Malaysian schools, offering opportunities for both personal and career development. Even though the English Proficiency Index Report 2019 indicated that Malaysia is ranked quite highly in terms of English language proficiency, the result does not represent the actual ability among many learners, especially in the rural areas, as Malaysian ESL learners face many difficulties in using English, verbally and in writing. Amidst the debate on Malaysian ESL learners’ proficiency level, it is important to measure how they perceive their ability to use English. This study intends to investigate Malaysian rural ESL learners’ perceptions of their English language proficiency. A survey research design was employed. Two hundred seventy-seven participants of Form 1, Form 3, Form 4, and Form 5 form rural schools in Malaysia who were recruited in this study. The data were gathered from a questionnaire based on the description of the Common European Framework of Reference for Languages (CEFR) ‘Self-assessment grid’. The interview was also conducted to support the quantitative data. The researchers analyzed the percentages, mean scores, and standard deviation of the questionnaire. Content analysis was employed to analyze the data from the interview session. Findings indicate that positive perceptions of English language learning enhance students’ interest, thereby accelerating their proficiency levels. This study offers insight into learners’ perspectives on their English language acquisition journey. Future research might consider employing a larger sample size and additional data collection instruments to enhance the significance of findings, particularly regarding ESL students’ perceptions of their English language proficiency.